Prevalence of oral precancerous and cancerous lesions in elderly Malaysians - Zain, R.B.; Ali, T.B.; Jalalluddin, R.L.; Abdul Razak, I. (SAGE Publications, 1996)
A house to house survey on elderly subjects aged 60 years old and above was undertaken in a large district in Malaysia. A total of 486 subjects in randomly selected Enumeration Blocks were interviewed and examined. The prevalence of oral precancerous lesions was recorded at 3.3%, of which leukoplakia was the most common. When the ethnic distribution of these oral precancerous and cancerous (OPC) lesions was compared, 72% of those inflicted were Indians. Oral cancer was detected in two subjects (0.4%), both of whom were of Indian origin. Among subjects with OPC lesions, 4.2% were smokers, 12.7% were betelquid chewers, 11.8% had indulged in both habits, whilst one subject had not practised any of the oral habits of interest (0.4%). The findings suggest the occurrence of OPC lesions to be related to betelquid chewing.